PENGARUH ALOKASI DANA DESA ( ADD ) TERHADAP KESEJAHTERAAN MASYARAKAT DESA AIR HANGAT KECAMATAN AIR HANGAT TIMUR KABUPATEN KERINCI: NANIK MANDASARI, S.IP., M.Si - nanik mandasari (LPPM STIA Nusantara Sakti, 2019)
Village funds allocation is a form of village right fulfillment to organize village autonomy in order to grow and develope to follow the village growth it self base on the diversity, partipatory, pure autonomy, democracy and empowerment of society. One of reasons why the village funds allocation (ADD) was needed and ADD wisedom in same line with regional autonomy note when the village placed as base of decentralize ADD wisedom realy relevant with perspective that placed the village as base of participation. formulation problem in this research is there any influences ADD to the society welfare in Air Hangat village at Air Hangat Timur district Kerinci regency and how far the influences, this research had done in air hangat timur kerinci regency. The population in this research were 312 KK and samples used 31 KK. This a quantitative research which used the numbering during the data collection, data overnmenton, and data presentation. The result of this research were there positive significant influences between village funds allocation to the society welfare of Air Hangat village Air Hangat Timur district Kerinci regency. The influences of village funds allocation (ADD) to the society welfare was 15,3%. As writer suggestion to the village overnment Air Hangat to more attention about overnment activities of monitoring and overnment to the ADD implementation in order to the ADD right targeted, then the village overnment Air Hangat also more attention of educational degrees and health services of society in order to the education or healt services will accessed easily by whole society elements.